(untitled) - Phillips, Todd S. (Hoboken, NJ., 2003)
Here's the in-depth information you need to initiate designs for a variety of justice facilities, including law enforcement, adult detention, courts, corrections, juvenile and family justice, and multi-occupancy facilities.
Keywords: Prisons,Correctional institutions,Nhà tù,Cải tổ; Design and construction,Design and construction,Thiết kế và xây dựng,Thiết kế và xây dựng; United States,United States,Hoa Kỳ,Hoa Kỳ